187k views
1 vote
Y=−6x+3 rewrite in standard form

User Htoniv
by
5.2k points

2 Answers

6 votes

Answer:

6x+y=3

Step by step:

Standard Form: Ax+By=C

Move Ax and By onto the same sides. y=-6x+3

-6x turns into a positive 6x because you are adding 6x onto both sides of the equation.

User FuryFart
by
5.7k points
4 votes

Answer:

6x + y = 3

Explanation:

The equation of a line in standard form is

Ax + By = C ( A is a positive integer and B, C are integers )

Given

y = - 6x + 3 ( add 6x to both sides )

6x + y = 3 ← in standard form

User Dhevendhiran M
by
5.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.